Students’ Translation Competence on Translating Figure of Speech from English to Indonesian: A case study - Azaria, Bella Erma (Language Horizon: Journal of Language Studies, 2022)
Knowing how to identify figures of speech, using translation strategies correctly, and having good translation competence are the qualifications to produce good translation products. This study pointed out student translators’ translation competence and translation strategies in figures of speech translation by applying the theories of translation strategies by Molina and Albir, figures of speech by Adam, and translation competence by Neubert. This study was designed as descriptive qualitative research. The data were taken from the documentation of students’ translation products of the poem "moonlight" and an online questionnaire answered by the participants, six student translators, with certain criteria. The result showed that, out of seven, there were six different figures of speech found. There were seven translation strategies applied by student translators out of 18 translation strategies. Not all of the strategies can be applied to any figures of speech due to the different nature of each of them. The last but not least, student translators have good subject competence and are mostly average in cultural competence but the two competencies do not go in line with transfer competence.